PERANCANGAN SISTEM INFORMASI PENJADWALAN SISTEM BLOK BERBASIS WEB PADA SMK PERMATA HARAPAN - Miftahul Ilmi; Hariselmi Hariselmi (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2021)
Abstract The preparation of a lesson schedule is a routine that is carried out by every educational institution, both official and unofficial. The block system is a scheduling system that aims to support learning achievement by using a complete learning method with a long duration every day. Permata Harapan SMK currently implements the block system as its scheduling system. The purpose of this research is to design a scheduling information system based on the block system at SMK Permata Harapan. the waterfall method was chosen as a method of developing the system. This method is a software development method that is systematic and sequential, the waterfall method is chosen as a system development method. This method is a software development method that is systematic and sequential. Data collection methods used are observation, interviews and literature study. The programming language implemented is PHP with the CodeIgniter framework accompanied by MYSQL as the data center. The implementation of the scheduling information system design at SMK Permata Harapan can simplify and provide benefits for the scheduling process and the smoothness of the teaching and learning process at SMK Permata Harapan. Keywords: Planning, Information Systems, Blocking Systems, CodeIgniter.